Amnioinfusion for the Management of Severe Oligohydramnios during the Second Trimester: A Retrospective Observational Study - Wei Gu; Xinrong Zhao; Yi Wu; Renyi Hua; Li Gao; Yanlin Wang (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: To evaluate the safety profiles and role of antepartum transabdominal amnioinfusion (TA) in detecting fetal anomalies in pregnant women with oligohydramnios during the second trimester. Methods: Pregnant women with a diagnosis of oligohydramnios at 16 0/7 to 27 0/7 weeks of gestation were evaluated at our center between June 2014 and April 2020. Data collected included maternal and fetal clinical characteristics, ultrasonographic or magnetic resonance imaging findings, chromosomal results, and perinatal mortality. Pregnancy outcomes and procedure-related complications were then analyzed. Results: The study analyzed 106 pregnant women with severe oligohydramnios, at a mean gestational age of 22+3 weeks. Out of these, 71 women received TA while the remaining 35 did not. Only two patients (2.82%) suffered adverse events of chorioamnionitis post-TA. Nineteen additional cases of fetal anomalies were detected following TA, leading to a significantly increased detection rate (24/71 vs 43/71, p = 0.001). Among the TA group, eight pregnancies without obvious fetal pathologies were delivered alive, and all newborns were discharged in good condition. Conclusions: TA is a safe and valuable procedure for pregnant women with severe oligohydramnios in the second trimester that improved the detection rate of fetal structural anomalies. TA may lead to favorable outcomes in pregnancies without obvious fetal pathologies.